2020
DOI: 10.3390/biomedicines8090345
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Toxicity Parameters Associated with Combustion Produced Soot Surface Chemistry and Particle Structure by in Vitro Assays

Abstract: Air pollution has become the world’s single biggest environmental health risk of the past decade, causing millions of yearly deaths worldwide. One of the dominant air pollutants is fine particulate matter (PM2.5), which is a product of combustion. Exposure to PM2.5 has been associated with decreased lung function, impaired immunity, and exacerbations of lung disease. Accumulating evidence suggests that many of the adverse health effects of PM2.5 exposure are associated with lung inflammation and oxidative stre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In the study of Totlandsdal et al (2010) , a concentration of 100 g/ml carbon exposure increased mRNA and protein expression of IL-1β and IL-6 in primary lung epithelial cells. Al Housseiny et al (2020) also said that IL-6 expression was increased in the bronchial tree during PM exposure ( Totlandsdal et al , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Totlandsdal et al (2010) , a concentration of 100 g/ml carbon exposure increased mRNA and protein expression of IL-1β and IL-6 in primary lung epithelial cells. Al Housseiny et al (2020) also said that IL-6 expression was increased in the bronchial tree during PM exposure ( Totlandsdal et al , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The participation of the nuclear factor erythroid 2-related factor 2 (Nrf2) in the oxidative stress triggered by PM has been extensively reported in recent years (Badran et al, 2020;Bagam et al, 2021;Housseiny et al, 2020;Ito et al, 2020;Liu et al, 2022b;Saha et al, 2022;Shi et al, 2023;Shrestha et al, 2021;Son et al, 2020;Tian et al, 2021;Wang et al, 2022aWang et al, , 2022bWang et al, , 2022cXue et al, 2021b). This is not surprising given the key role of Nrf2 in the protection against oxidative stimuli (Saha et al, 2020), acting as a sensor to protect the cells against oxidative damage induced by PM-generated ROS.…”
Section: Nrf2: the Master Regulator Of Antioxidant Responsementioning
confidence: 96%
“…In vitro cell studies have shown that exposure to soot, secondary organic aerosols (SOA) and diesel exhaust (DE) particles causes pro-inflammatory responses, including increased release of IL-6 and IL-8 [ 49 ]. Bronchial epithelial cells exposed to functionalized carbon black show increased mRNA levels of IL-1β and IL-6 [ 50 ] and bronchial epithelial cells exposed to SOA show increased levels of released IL-8 [ 51 ]. IL-6 from leucocytes, endothelial cells, keratinocytes and fibroblasts has been shown to play a significant role in acute inflammation and adaptive tissue remodelling [ 52 ].…”
Section: Respiratory Responses To Aerosol Exposurementioning
confidence: 99%
“…Altogether, IL-6 is acknowledged to be an important biomarker of the acute inflammatory response to particulate pollution. Elevated levels of IL-6 have been observed following PM exposure in in vitro [ 50 ] and in vivo [ 46 , 54 ] studies, as well as in blood samples from healthy volunteers under experimental and real-world exposure conditions [ 61 , 63 ]. This illustrates the relevance and coherence of in vitro and in vivo toxicology studies to real-world effects in humans.…”
Section: Respiratory Responses To Aerosol Exposurementioning
confidence: 99%